2007
DOI: 10.1590/s0100-40422007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Atividade acaricida dos óleos essencias de folhas e frutos de Xylopia sericea sobre o ácaro rajado (Tetranychus urticae Koch)

Abstract: Recebido em 13/4/06; aceito em 30/8/06; publicado na web em 26/3/07 ACARICIDAL ACTIVITY OF the ESSENTIAL OILS OF LEAVES AND FRUITS OF Xylopia sericea St. Hill. ON THE TWO SPOTTED SPIDE MITE (Tetranychus urticae Koch). The essential oils of the leaves and fruits obtained by hydrodistillation of Xylopia sericea, collected in the restinga area of Pernambuco, were analyzed by GC (HP 5890 SERIES II) and GC/MS (HP 5890B SERIES II/ MSD 5971). A major part of the volatile components identified in the oils of fruits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
(16 reference statements)
1
14
0
3
Order By: Relevance
“…The ability of essential oils to reduce fecundity in T. urticae has been reported in previous studies analyzing fumigant toxicity (Pontes et al, 2007a;2007b;, but with no indication as to whether this reduction in fecundity was due to the properties of the oils or the death of mites. In the present study, the results of the fecundity experiments demonstrated that T. urticae females exhibited a behavioral response to the essential oil vapors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ability of essential oils to reduce fecundity in T. urticae has been reported in previous studies analyzing fumigant toxicity (Pontes et al, 2007a;2007b;, but with no indication as to whether this reduction in fecundity was due to the properties of the oils or the death of mites. In the present study, the results of the fecundity experiments demonstrated that T. urticae females exhibited a behavioral response to the essential oil vapors.…”
Section: Discussionmentioning
confidence: 90%
“…This is the first report of the fumigating action of P. marginatum oils on T. urticae and its natural enemy N. californicus. However, the evaluation of the acaricidal activity of other plant species against T. urticae has been investigated previously, such Protium bahianum, Protium heptaphyllum (Pontes et al, 2007a;, Xylopia sericea (Pontes et al, 2007b), Citrus sinensis, Citrus aurantium (Araújo-Júnior et al, 2010), and Piper aduncum (Araújo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…O cubenol (7,43 a 13,67%) foi outro constituinte majoritário identificado nos óleos de P. neochilous. Este constituinte apresentou atividade acaricida contra ácaro rajado (Tetranychus urtiae Koth) (Pontes et al, 2007).…”
Section: Teor Rendimento E Identificação Da Composição Química Dos óunclassified
“…FEITOSA et al (2009) characterized the essential oil present in the branches of Rollinia leptopetala, lacking monoterpenes, whereas sesquiterpenes, particularly oxygenated sesquiterpenes, were abundantly present. PONTES et al (2007) evaluated the acaricidal activity of the essential oil obtained from the leaves of Xylopia sericea; ~95% of the oil comprised of a complex mixture of sesquiterpenes. CAMPOS et al (2014) also reported a predominance of sesquiterpenes in the essential oils of Annona emarginata and Annona squamosa.…”
Section: -----------------------------------------Area (%)-----------mentioning
confidence: 99%
“…The Cerrado is home to 10 genera and 47 species, none of which is endemic to the area, even though some of the genera and species are quite common, such as Annona crassiflora, Duguetia furfuracea, Xylopia aromatica, and Cardiopetalum place with respect to the number of species per family in the Cerrado. Some genera are chemically welldocumented, such as Xylopia, where significant concentrations of caryophyllene oxide, α-pinene, α-terpinene, limonene, spathulenol, germacrene-D, trans-β-guaiene, and β-caryophyllene are present in the essential oils extracted from the leaves and fruits (SANTOS, et al 2004;PONTES et al, 2007;VALTER et al, 2008). Annona genus has also been well-characterized; caryophyllene, camphene, α-pinene, and β-pinene have been identified in the essential oil extracted from the leaves (BANDEIRA et al, 2011;CAMPOS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%